Effects of Drought and Low Nitrogen Stress on Provitamin A Carotenoid Content of Biofortified Maize Hybrids. Issue 6 (1st November 2019) - Ortiz‐Covarrubias, Yadhira; Dhliwayo, Thanda; Palacios‐Rojas, Natalia; Ndhlela, Thokozile; Magorokosho, Cosmos; Aguilar‐Rincón, Victor H.; Cruz‐Morales, Andrea S.; Trachsel, Samuel
ABSTRACT: Maize ( Zea mays L.) hybrids with enhanced provitamin A (proVA) content have been deployed in sub‐Saharan Africa, where low soil nitrogen and drought stress are common. The objectives of this study were to assess: (i) the effects of drought and low‐N stress on grain proVA content of hybrids with enhanced proVA content, and (ii) the inheritance of proVA carotenoids under these stress conditions. An 11‐line diallel cross (55 F1 crosses) was evaluated for carotenoid content and grain yield under optimum conditions, drought, and low‐N stress. Compared with the optimum treatment, mean proVA was lower under both stress treatments. The consistency of genetic effects across stress treatments suggested that hybrids with improved proVA content can be developed for a broad range of environments, provided they are sufficiently adapted. General combining ability (GCA) was significant ( P < 0.01), and accounted for >85% of the variation among hybrids, whereas specific combining ability (SCA) effects were generally weak ( P < 0.05), accounting for 5 to 15% of hybrid sums of squares across the three treatments. These results indicated that the inheritance of proVA was not affected by stress treatments. A negative correlation between grain yield and proVA carotenoids was detected, but the data suggested that it was caused by the genetic background of the germplasm used rather than pleiotropy. Our results provide insights that may help breeders design effective breeding strategies to develop proVA‐enriched cultivars for resource‐limited farming systems.